2012
DOI: 10.1002/adma.201203161
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Hexahapto Functionalization of Single Layer Graphene as a Route to High Mobility Graphene Devices

Abstract: Pristine single layer graphene (SLG) has exceedingly high mobility, which is ∼ 4,000-20,000 cm 2 /Vs for typical devices supported on Si/SiO 2 substrates, and may reach as high as 250,000 cm 2 /Vs in suspended devices at room temperature. [ 1 ] Such high mobilities make graphene an extremely attractive candidate for the next generation electronic materials. However, the absence of a band gap, which is necessary for digital electronics, presents a technological challenge. One effective approach to band gap engi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 43 publications
6
75
0
Order By: Relevance
“…Yield: 69.6%. 6 , (C 7 H 8 )M(CO) 3 , or (C 6 H 6 )Cr(CO) 3 This protocol was adapted from the literature [40]. In a general procedure, SWCNTs (0.04 g) were placed in a Schlenk flask equipped with a stir bar and were heated at 100 • C under vacuum overnight.…”
Section: Microwave/hcl Treatment Of Swcntsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield: 69.6%. 6 , (C 7 H 8 )M(CO) 3 , or (C 6 H 6 )Cr(CO) 3 This protocol was adapted from the literature [40]. In a general procedure, SWCNTs (0.04 g) were placed in a Schlenk flask equipped with a stir bar and were heated at 100 • C under vacuum overnight.…”
Section: Microwave/hcl Treatment Of Swcntsmentioning
confidence: 99%
“…The wafer was diced up into 1.0" × 0.5" coupons. Exfoliated graphite, (CH 3 CN) 3 M(CO) 3 , and (C 7 H 8 )M(CO) 3 (M = Cr, W) were prepared according to the methods presented in the literature [39,40]. All solvents were distilled (unless they were obtained from the solvent purification system) and degassed.…”
Section: Materials and Characterizationmentioning
confidence: 99%
“…In fact, a large increase in D-band intensity was indeed observed experimentally [6] upon formation of the Bz|M|Gr complexes, possibly indicating complex-formation at the defect sites. Sarkar et al [6,7] also reported a decrease in conductance upon complex formation for a related structure, Gr|M|(CO) 3 , that is isoelectronic to the sandwich structures of interest here. Although the aforementioned experimental works did not report the transport properties of the Bz|M|Gr complexes themselves, the reported loss of conductivity for the related structures is also consistent with the complex-formation at defect sites.…”
mentioning
confidence: 98%
“…However, experimentally, it has proven harder to create such complexes [10]. There is only a single report for these specific complexes [6], although some related structures were recently reported [7,11]. Some of the difficulties encountered in creating these structures stem from: (a) the high mobility of TMs on graphene, and (b) the high cohesive energies of the TMs [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation